The safety and efficacy of laparoscopic common bile duct exploration for the management of choledocholithiasis after endoscopic retrograde cholangiopancreatography failure: an observational study carried out in Al-Azhar University Hospital in Assiut - Mohamed A.A.Abd A.A.Abd Alrahem Abed; Ahmed M.H Ahmed; Karim M.N.T Kamel (Wolters Kluwer Medknow Publications, 2020)
Background objective To assess the efficacy of laparoscopic common bile duct exploration (LCBDE) (in conjunction with laparoscopic cholecystectomy) as a single-stage operation to manage CBD stones failed to be extracted by endoscopic retrograde cholangiopancreatography (ERCP) and to evaluate the possible complications related to CBD stones. Patients and methods The study includes 30 patients diagnosed as having CBD stones proved clinically and through laboratory investigations in the form of obstructive jaundice and confirmed radiologically using hepatobiliary ultrasound and magnetic resonant cholangiopancreatography. All patients had a failed trial of ERCP stone extraction. They had a mean age of 51.067±11.32 years, and 40% of patients were males versus 60.0% were female. Results Postoperative follow-up was done after 1 week in the study group. Regarding postoperative ultrasound, 93.3% of patients had clear duct. Moreover, there was no pancreatitis in 96.7% of patients. Regarding cholangiogram, 93.3% had no stone. The mean hospital stay was 2.60 days, and 46.7% of the patients had a duration of staying at hospital of 2 days and 33.3% of patients had 3 days. Conclusion Laparoscopic bile duct exploration has achieved acceptance among the surgeons as a substitution to ERCP for management of CBD stones. Although its safety and successfulness are already confirmed among young patients in the elective setting, this study points to the rising proof of its safety among the elderly patients, in both elective and emergency settings. In centers that are capable of offering LCBDE to patients with CBD stones, LCBDE should be attempted in elderly patients observed to be fit for laparoscopic cholecystectomy.